Type 2 Diabetes Leads to Axon Initial Segment Shortening in db/db Mice - Yermakov, Leonid M.; Drouet, Domenica E.; Griggs, Ryan B.; Elased, Khalid M.; Susuki, Keiichiro (Frontiers in Cellular Neuroscience, 2018)
Cognitive and mood impairments are common central nervous system complications of type 2 diabetes, although the neuronal mechanism(s) remains elusive. Previous studies focused mainly on neuronal inputs such as altered synaptic plasticity. Axon initial segment (AIS) is a specialized functional domain within neurons that regulates neuronal outputs. Structural changes of AIS have been implicated as a key pathophysiological event in various psychiatric and neurological disorders. Here we evaluated the structural integrity of the AIS in brains of db/db mice, an established animal model of type 2 diabetes associated with cognitive and mood impairments. We assessed the AIS before (5 weeks of age) and after (10 weeks) the development of type 2 diabetes, and after daily exercise treatment of diabetic condition. We found that the development of type 2 diabetes is associated with significant AIS shortening in both medial prefrontal cortex and hippocampus, as evident by immunostaining of the AIS structural protein βIV spectrin. AIS shortening occurs in the absence of altered neuronal and AIS protein levels. We found no change in nodes of Ranvier, another neuronal functional domain sharing a molecular organization similar to the AIS. This is the first study to identify AIS alteration in type 2 diabetes condition. Since AIS shortening is known to lower neuronal excitability, our results may provide a new avenue for understanding and treating cognitive and memory impairments in type 2 diabetes.